ALVAREZ, Marcos César; MISKOLCI, Richard; SCAVONE, Lucila (Orgs.). O legado de Foucault. - Nichnig, Claudia Regina (Revista Estudos Feministas, 2008)
ALVAREZ, Marcos César; MISKOLCI, Richard; SCAVONE, Lucila (Orgs.). O legado de Foucault.